2018
DOI: 10.1016/s2468-1253(17)30404-1
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir and velpatasvir for hepatitis C virus infection in people with recent injection drug use (SIMPLIFY): an open-label, single-arm, phase 4, multicentre trial

Abstract: Gilead Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
169
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 36 publications
27
169
3
1
Order By: Relevance
“…The use of HCV testing interventions such as alerts and patient solicitation methods has demonstrated improvement in screening and diagnosis rates in some centres . Our finding of excellent outcomes in PWID with no increase in LTFU compared to the general population supports current guidelines that ongoing drug should not preclude treatment …”
Section: Discussionsupporting
confidence: 73%
“…The use of HCV testing interventions such as alerts and patient solicitation methods has demonstrated improvement in screening and diagnosis rates in some centres . Our finding of excellent outcomes in PWID with no increase in LTFU compared to the general population supports current guidelines that ongoing drug should not preclude treatment …”
Section: Discussionsupporting
confidence: 73%
“…Previous analyses of DAA regimens have demonstrated high adherence to treatment in the overall chronic HCV‐infected patient population, including those who were on opioid substitution therapy (OST) and people who use drugs (≥95% and ≥90% respectively). Some studies have suggested that adherence to DAA therapy decreases with increased treatment duration .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment uptake has been historically low among PWID prior to the introduction of new direct‐acting antivirals (DAA) treatments . However, there is now good evidence that HCV treatment is safe and effective among PWID . The latest international guidelines now recommend treatment for all PWID.…”
Section: Introductionmentioning
confidence: 99%